A reader, researcher, interpreter, ‘co-author’ (based on the materials of the works of Andrey Bely about Russian writers of the 19th century – the beginning of the 20th century) - Лосиевский, Игорь Яковлевич (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
Theoretical problems of correlation between a reader and a text: a paradigm of reader’s perception and interpretation, the limits of the research interpretation and the peculiarities of ‘co-creative’ interpretation of the text are considered in the article. Specific features of the research interpretation and elements of ‘co-creation’ in literary studies and critical works of Andrey Bely were analysed.